Transitioning and Sustaining Community Connection During COVID - Carlson, Catie; Ladell, Kathy (Marketing Libraries Journal, 2021)
Entering a higher education institution as a new library employee often means identifying your role, allies, and methods to reach the community served. Identifying and reaching out becomes even more challenging when employee attrition results in a large loss of institutional knowledge. When the COVID-19 pandemic forced an academic library to shut down physical services, traditional means of establishing relationships with the community were further complicated. This case study explores this library’s successes and failures in reaching out to a community during the high stress, remote teaching and learning situation brought on by the pandemic. The authors conclude that successful community-building should emphasize people and synchronous social interaction for the greatest impact.